(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
Currently, experiments conducted around the world, including Brazil, have already proven the robustness of PowerLine Communication (PLC), indicating that this technology can offer a broad spectrum of applications, from access to broadband Internet, telephony, tele-control, home automation, audiovisual services, building security, among others, promoting the integration of different services on a single physical medium, being one of the VoIP application. This study aims to present an analysis on the technology that enables data and transmit electricity in the same physical environment, the PLC. Therefore, in order to prove the quality of this method was presented some studies for the provision of telephony through Voice over IP (VoIP), confirming the position of the PowerLine Communication as an alternative access network telecommunications.